Web-Based Boarding School Monitoring System - Norsuzila Ya’acob; Aziean Mohd Azize; Azita Laily Yusof; Suzi Seroja Sarnin; Nani Fadzlina Naim; Siti Norbaiyah Rohaizad (Institute of Advanced Engineering and Science, 2018)
An alibi is a priceless thing that someone can rely on when in needs. A good data management can and will save someone life in respond to any unwanted situation.A simple, accurate and trustworthy data log for students in boarding school can and will help ease parent-teacher monitoring system. However, the conventional system require student to manually inform and record their log to their parents and teachers. The system is lacks of automation where a number of problem may arise. The problem includes the inaccurate logging time, misplace of outing card and an unorganized log record. Web-Based Boarding School Monitoring System (WEBMOS) Using MySQL Database and RFID Technology were invented to solve this problem. This technology offered a system that can record student log data in an accurate manner. The aim is to build a system that can provide the accurate data to parent and teacher via a single click through their personal device. This system uses RFID module technology to monitor the student’s logs activity in real time manner. The monitoring system involve the utilization of Arduino Mega, Ethernet Shield, Global System for Mobile communication (GSM) and Radio Frequency Identification (RFID) Module. The system performs an automated data log after the student flashed their card to RFID reader, the data is uploaded to database after the card being flashed and the uploaded information can be view at the webpage at anywhere and anytime. Thus, thesystem is capable of collecting and recording aprecise real time data logging for student’s activity.